Evolution of corneal epithelial remodeling after myopic laser in situ keratomileusis surgery measured by anterior segment optical coherence tomography combined with Placido disk - Díaz-Bernal, José Manuel; García Basterra, Ignacio; Mora-Castilla, Jose; Nguyen, Annie; Fernandez-Barrientos, Yolanda; Guerrero, Antonio M. (Indian journal of ophthalmology, 2022)
Purpose: To investigate patterns of short- and long-term variations in corneal epithelial thickness (CET) after myopic laser in situ keratomileusis (LASIK) using anterior segment optical coherence tomography (AS-OCT) combined with Placido disk-based topography. Methods: In this retrospective study, 36 subjects (72 eyes) who underwent LASIK myopic surgery and 53 healthy subjects (106 eyes) who served as controls were enrolled. AS-OCT (MS-39) was performed in all patients before, 1 day, 1 month, and 6 months after surgery. Statistical analysis was performed to analyze CET changes over time after LASIK and to detect patterns of definitive CET remodeling compared to healthy subjects. Multivariate analysis was performed to look for possible predictors of final CET. Results: There was no statistically significant difference between groups in terms of demographic and anterior segment parameters (all P > 0.05). After LASIK, all sectors and rings got thicker over time (1.62–8.32 μm; P < 0.01). Except for the central sector, all areas achieved the thickest CET value one day after surgery with a progressive epithelial thinning between 1 and 6 months of follow-up. Changes on CET occurred independently of the grade of myopia before LASIK or final refraction (P > 0.05). None of the clinical variables studied, including diopters corrected, were found to be correlated with final CET (P > 0.05). Conclusion: Independent of anterior segment parameters and diopters corrected, CET becomes thicker after LASIK surgery. Central and inner ring sectors thicken more than those more peripheral. CET remodeling after myopic LASIK should be taken into consideration when planning refractive surgery.
Keywords: Corneal epithelium; keratomileusis; laser in situ; myopia; optical coherence tomography; refractive surgeries procedures; JCR